A TINGKAT KEPERCAYAAN MASYARAKAT TERHADAP PENGGUNAAN APLIKASI BELANJA ONLINE: TINGKAT KEPERCAYAAN MASYARAKAT TERHADAP PENGGUNAAN APLIKASI BELANJA ONLINE - Rachmawaty Djaffar (Program Studi Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2021)
This study aims to determine the level of public confidence in online shopping applications and the level of satisfaction of people shopping online. This research uses a descriptive-argumentative quantitative method using a survey approach. The distribution of questionnaires was distributed to respondents through the Google Form application, with 102 respondents. Questions asked using a Likert scale. In order to be calculated in a quantitative form, the answers of the respondents can be given a weight value or Likert score. The results showed that in relation to trust, based on a recapitulation of the answers to five indicators related to the aspect of trust, it was found that all indicators gave an 'agreed' answer to the statement given. This means that respondents generally have a high level of confidence to shop at the Online Marketplace or Online Shop, where the average answer index is in the range of 60% - 79.99%. Regarding this aspect of satisfaction, all indicators show the answer ‘agree; which means that the majority of respondents said they were satisfied with services where the average answer index was in the range of 60% - 79.99%.